Periacetabular bone metabolism following hip revision surgery - Bernstein, P.; Beuthien-Baumann, B.; Kotzerke, J.; Hofheinz, F.; Zessin, J.; Stiehler, M.; Günther, K.-P. (Nuklearmedizin - NuclearMedicine, 2014)
The treatment of loosened total hip replacement (THR) acetabular components may require the management of severe bone defects. Although being applied for decades, there is only limited scientific data about the osteointegration of cancellous bone allografts (CBA) and other void fillers. Monitoring of periprosthetic bone regeneration could possibly help to optimize this process thereby reducing late failure rates. The aim of this study was to show osteometabolic changes in periprosthetic CBA after THR revision with the use of sodium-[18F]-fluoride (NaF) and positron emission tomography (PET). Patients, methods: Twelve patients undergoing THR revision with the use of CBA were prospectively enrolled in the study. Nine patients completed all necessary examinations and were included in the evaluation. The temporal pattern of osteointegration was assessed via NaF-PET at one (PET1) and six weeks (PET2) after surgery. CBA, tantalum implants, supraacetabular regions ipsilateral and contralateral, and parasymphyseal pubic bones were delineated as volumes of interest (VOI) in postop CT scans, which were then merged with the PET data. Results: In comparison to the contralateral supraacetabular reference bone, a significant 1.5-fold increase of osteometabolic activity from PET1 to PET2 was seen in the CBA region. Also, the ipsilateral supraacetabular host bone showed a higher NaF-in- flux in week 6, compared to the first postoperative week. The supraacetabular site exhibited a significantly 1.8- to 2-fold higher influx and uptake than bone regions in non-operated sites. Tantalum implants had a low NaF influx at both time points investigated. Conclusion: Using NaF-PET osteometabolic changes of CBA and implant- bone-interfaces can be monitored. Applying this method we demonstrated early periprosthetic temporal bone regeneration patterns in THR cup revision patients.
Keywords: Allograft; NaF-PET; bone metabolism; endoprosthesis; acetabular